Spin‐Labeled Riboswitch Synthesized from a Protected TPA Phosphoramidite Building Block. Issue 56 (18th August 2022) - Kaiser, Frank; Endeward, Burkhard; Collauto, Alberto; Scheffer, Ute; Prisner, Thomas F.; Göbel, Michael W.
Abstract: The nitroxide TPA (2, 2, 5, 5‐tetramethyl‐pyrrolin‐1‐oxyl‐3‐acetylene) is an excellent spin label for EPR studies of RNA. Previous synthetic methods, however, are complicated and require special equipment. Herein, we describe a uridine derived phosphoramidite with a photocaged TPA unit attached. The light sensitive 2‐nitrobenzyloxymethyl group can be removed in high yield by short irradiation at 365 nm. Based on this approach, a doubly spin‐labeled 27mer neomycin sensing riboswitch was synthesized and studied by PELDOR. The overall thermal stability of the fold is not much reduced by TPA. In‐line probing nevertheless detected changes in local mobility. Abstract : The nitroxide TPA (2, 2, 5, 5‐tetramethyl‐pyrrolin‐1‐oxyl‐3‐acetylene) has been protected with a light sensitive 2‐NBOM group and connected to a uridine phosphoramidite building block. Spin‐labeled RNA can be obtained from this compound by standard protocols of oligonucleotide synthesis and used for EPR studies after light‐induced deprotection.